2017
DOI: 10.1016/j.tifs.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

KEAP1 and done? Targeting the NRF2 pathway with sulforaphane

Abstract: BackgroundSince the re-discovery of sulforaphane in 1992 and the recognition of the bioactivity of this phytochemical, many studies have examined its mode of action in cells, animals and humans. Broccoli, especially as young sprouts, is a rich source of sulforaphane and broccoli-based preparations are now used in clinical studies probing efficacy in health preservation and disease mitigation. Many putative cellular targets are affected by sulforaphane although only one, KEAP1-NRF2 signaling, can be considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(154 citation statements)
references
References 144 publications
(180 reference statements)
4
148
0
2
Order By: Relevance
“…It has been reported that SFN can combat cancer by multiple mechanisms, including induce Nrf2 activation [36], epigenetic modulation of oncogenic MicroRNA-21 and human telomerase reverse transcriptase (hTERT) [37], inhibition of histone deacetylase (HDAC) [38] and NF-κB [39]. However, its anti-tumor effect on pancreatic cancer, especially under high glucose conditions, has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that SFN can combat cancer by multiple mechanisms, including induce Nrf2 activation [36], epigenetic modulation of oncogenic MicroRNA-21 and human telomerase reverse transcriptase (hTERT) [37], inhibition of histone deacetylase (HDAC) [38] and NF-κB [39]. However, its anti-tumor effect on pancreatic cancer, especially under high glucose conditions, has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Aflatoxin is activated in the liver and alkylates cellular components, inducing mutations and cancer development (59). Electrophilic drugs targeting activation of Nrf2 induce the expression of over 100 Phase 2 genes, thus allowing for more efficient detoxification of aflatoxin and protection against carcinogenesis (60,61). In this regard, Evgen Pharma has now successfully stabilized sulforaphane using an α-cyclodextrin-based formulation, a key step towards the evaluation of sulforaphane in clinical trials.…”
Section: No2-fa Therapy At the Intersection Of Other Successful Pharmmentioning
confidence: 99%
“…Because of its presence in consumable food, sulforaphane is an attractive candidate for further human study. Indeed, its potential utility has been demonstrated in the treatment of asthma, air pollution injury, benign prostate hyperplasia, UV-induced erythema, diabetes, the control of Helicobacter pylori (a stomach carcinogen), and potentially in the prevention of a number of different cancers [42-44]. Furthermore, recent reports have suggested that administration of sulforaphane leads to beneficial outcomes of human brain disorders such as autism and SZ [45-47].…”
Section: Introductionmentioning
confidence: 99%